Radioisotope Analyses in Determination of Time since Death from Skeletal Remains - Ünlütürk, Özge (The Bulletin of Legal Medicine, 2016)
Estimation of the time since death is one of the most important problems in forensic cases. It is relatively easier to estimate the time since death in such cases if the corpse is fresh or the soft tissue still exists. However, estimating postmortem interval becomes more complicated as decomposition stage of the corpse develops. While evaluating decomposition stages of a corpse, different criteria like environmental conditions, position of the body and bodily features should be studied all together. Estimation of the time since death is carried out macroscopically in the first place according to morphological changes. Nevertheless, various histological, chemical and psychical methods can be used as well to estimate the time since death particularly if long time passes after death and skeletonization begins. Of all these methods, radioisotope analyses are the most discussed method since it is not affected by environmental factors. Because of their short half-lives, the analyses especially carried out with measurement of Sr90and Pb210radionuclides have produced successful results in estimating postmortem intervals.
Keywords: time since death; radioisotope analysis; nuclear testing; Sr90; Pb210